Tineiden aus Afghanistan mit einer Revision der paläarktischen Scardiinen (Lepidoptera: Tineidae). - Petersen, Günther (Contributions to Entomology = Beiträge zur Entomologie, 1959)
The above publication deals with the results of the investigations on 123 specimens of Tineidae collected by the German Afghanistan Expedition 1956. 14 new species are described and figured as to their genitalia. One of them, a new species of Morophaga H.-S., has led to a revision of the Scardia-group, which has recently been splitted into several genera. There is dicussed the author's conclusion that only three of them (Scardia Tr., Morophaga H.-S., and Morophagoides Pet.) can be conserved, the others (MicroscardiaAms. and Montescardia Ams.) falling into synonymy as like as Atabyria Snel. (Acrolepiidae), the type and only known species of which (bucephala Snel.) from Ussuri district and Japan being a true Morophaga. Nomenclatural Actsafghana Petersen, 1959 (Catabola), spec. n.amseli Petersen, 1959 (Catabola), spec. n.obscura Petersen, 1959 (Catabola), spec. n.sarobiella Petersen, 1959 (Catabola), spec. n.luteola Petersen, 1959 (Episcardia), spec. n.pygmaeana Petersen, 1959 (Episcardia), spec. n.minuta Petersen, 1959 (Haplotinea), spec. n.nigrocapitella Petersen, 1959 (Morophaga), spec. n.flavifrons Petersen, 1959 (Nemapogon), spec. n.fasciata Petersen, 1959 (Neurothaumasia), spec. n.asiatica Petersen, 1959 (Pachyarthra), spec. n.orientalis Petersen, 1959 (Paratinea), spec. n.sarobiella Petersen, 1959 (Paratinea), spec. n.Atabyria Snellen, 1884 (Tineidae), syn. n. of Morophaga Herrich-Schäffer, 1853Microscardia Amsel, 1951 (Tineidae), syn. n. of Morophaga Herrich-Schäffer, 1853Montescardia Amsel, 1951 (Tineidae), syn. n. of Scardia Treitschke, 1830